Analisis Strategi Bisnis pada Toko Budiman Sembako Kecamatan Sungai Tebelian, Kalimantan Barat: strategi bisnis - Andri lolo (J-MD Jurnal Manajemen Dakwah, 2022)
Budiman's grocery store is a shop that sells various kinds of fresh fruits. Due to the tight competition in the food trade, this shop has its own business strategy. Business strategy aims to achieve long-term goals to be achieved and find the company's position in the industry so that the company can protect itself against competitive pressures. This study aims to analyze business strategies in surviving the pressure of intense competition, specifically the Budiman Sembako shop in Penjernang village. This research was conducted using descriptive qualitative methods by prioritizing interview methods and observation instruments, namely direct observations and assisted by literature studies. This research was conducted by analyzing the external environment and the internal environment through business functions. Then do a SWOT analysis, so that it can produce several alternatives in developing a business strategy for Budiman's grocery store. The results of this study indicate that the right strategy for the Budiman Sembako shop is the intensive strategy. With these alternative strategies the company can achieve the desired goals and can survive in the face of competitive pressures in the market. Keywords: Business Strategy, Business Environment, and SWOT Analysis